CONCENTRATIONS TEST OF METHANE GAS FROM SWAMP FORAGE SILAGE WITH IN VITRO METHOD - Sarno Sarno; Moh. Rasyid Ridho; Dwi Puspa Indriani; Harmida Harmida; Adelia Rizki Pancasari (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2017)
Aims of this study to concentration test of methane gas from swamp forage silage with in vitro methods.This study used Completely Randomized Design with 3 treatments and each treatment consisted of 5 replications. The treatments used are as follows: P1 (100% kumpai tembaga grass (Hymenachne acutigluma)), P2 (50% kumpai tembaga grass (Hymenachne acutigluma) + 50% kemon air (Neptunia oleracea lour)), P3 (100% kemon air ( Neptunia oleracea lour)). The parameters observed N-Ammonia, total gas production, methane gas concentrations in vitro and VFA partially. The results of variance showed that treatment significantly different (P <0.05) with methane concentration in vitro with highest gas concentration treatment of silage made from 50% kumpai tembaga grass (Hymenachne acutigluma) and 50% kemon air (Neptunia oleracea lour).Keywords: Concentration, Methane, Silage Forage Swamp, In Vitro.